Student Engagement Within Adolescent Reading Comprehension Interventions: A Systematic Literature Review. Issue 2 (April 2023) - Anderson, Leah L.; Meline, McKenzie; Harn, Beth
The purpose of this study was to complete a systematic review of the adolescent comprehension intervention research published between 2000 and 2020 to examine the presence of instructional practices to promote student engagement. Ninety-five studies were coded and indicated that 93% of the studies included at least one instructional practice and only 15% of studies actually measured engagement. Few studies (6%) examined the relationship between engagement and outcomes; studies that incorporated instructional practices to promote engagement demonstrated a statistically significant relation to engagement. Although student engagement is accepted as important in reading, it is rarely assessed within intervention efforts.